Routine Recitation Activities Can Improve People’s Religious Behavior - Zahira, Safna Tiara; Aisyah, Nurul (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Routine recitation which is a religious activity as a forum for the implementation of Islamic education for the community, which hopes to produce humans with good religious behavior. The purpose of this study was to determine the relationship between routine recitation and the religious behavior of the people of Sokanandi village, Banjarnegara as well as to analyze their religious behavior. This research uses the methodMixed Methode. Population and research sample taken usingsimple random sampling, namely the Sokanandi village community who attended routine recitation as many as 40 respondents. The research instrument used questionnaires, observations, and interviews. Quantitative data analysis using correlation testproduct moment, While the qualitative data was taken from the results of interviews with five informants consisting of ustadz, as well as regular recitation congregations. The results of the research on the significance of the independent variables, namely routine recitation and the dependent variable, namely the religious behavior of the community, is 0.00 <0.01, which means that H0 is rejected. and it was stated that there was a relationship between routine recitation and the religious behavior of the community and there was an increase in the religious insight of the congregation, so that the jam'ah had better quality religious behavior. It is hoped that with this research, recitation institutions can increase religious activities and recitation facilities, as well as for congregations to remain consistent and be able to invite the surrounding community to attend regular recitations.